Business Plan : Hibriyah Unisex Hair Saloon Enterprise / Alim Muaz Mahadi...[et al.] - Mahadi, Alim Muaz; Abdullah, Arifah Awatif; Yaakob, Farzana Aqilah; Ku Mohd Sabri, Ku Nazzatul Alia; Mohd Rasdi, Nur Amanina (2010)
Hibriyah Unisex Hair Salon Enterprise is a form of business based on partnership which consist of five members which hold important position such as General Salon Manager,Marketing Manager,Financial Manager, Senior Hair Stylist and Salon’s Receptionist.The business capital is fully loan amounted RM 242913 from Bank Islam Berhad. This company provides unisex haircuts, straightening, hair washing, hair coloring, and curly hair. Hibriyah Unisex Hair Salon Enterprise with motto of ‘From Head To Heart’ is located at Sungai Petani with address No 31A, Jalan Tiga, Pusat Perniagaan Pekan Lama, 08000, Sungai Petani, Kedah,Malaysia.. This company also offers sell side products to generate more income such as Pomade, hair straightening oil and hair conditioner which is wanted by the customer nowadays as it is easy to consume and have multi-function. We have done some research that Sungai Petani is one developed state which consist of the people with lower income level and higher income level. Thus, we recommended this salon with all type of income level as the prices of our services and products is reasonable and affordable.